The Impact of Covid-19 Pandemic on the Global Economy: Emphasis on Poverty Alleviation and Economic Growth - Vitenu-Sackey, Prince Asare; Barfi, Richard (The Economics and Finance Letters, 2021)
The COVID-19 pandemic has devastated the global economy, which has rendered many of the world’s population impoverished. Moreover, the pandemic has generated some uncertainties regarding economic and social policies. This phenomenon is lately the brunt of every government across the globe. This present study seeks to evaluate the pandemic’s impact on poverty alleviation and the global GDP by considering individual countries’ heterogeneous effects in a panel study. The motivation is to unravel the social and economic effects on the global economy. However, 170 countries are utilized in this study, and econometric panel techniques such as OLS and robust least square regression methods are utilized. The data was collected from OurWorldindata.com, comprising total COVID-19 cases, total deaths, stringency index, human development index, and gross domestic product per capita. The study’s findings stipulate that many people’s stringency and the contraction of the disease have inversely affected poverty alleviation and economic growth. Nevertheless, for the deaths recorded so far positively affects both poverty alleviation and economic growth. This development signals the essence of controlling population growth as it impedes economic growth and poverty alleviation. The study recommends that governments invest in health and education improvement and stimulate their economies to create employment that could propagate growth to improve poverty alleviation and economic growth.